Light weight and high performance electro magnetic shielding material and Manufacturing method thereof
Patent Information
- Application Number
- KR1020250128125
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2045-09-09
Smart Images

Figure 112025103497702-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a lightweight high-performance electromagnetic shielding material and a method for manufacturing the same. More specifically, the invention relates to a lightweight high-performance electromagnetic shielding material and a method for manufacturing the same, wherein an amorphous metal sheet layer having electromagnetic wave absorption properties is formed to reduce secondary electromagnetic damage caused by a magnesium plate, which is an electromagnetic shielding metal, thereby enabling simultaneous reflection and absorption of electromagnetic waves.
[0002] Furthermore, this invention is a result of the research conducted under the Defense Industry Specialized Development Research Institute Establishment and Operation (No. DC2023SD) project supported by the Defense Technology Promotion Research Institute. Background Technology
[0004] Recently, there has been a trend of rapid expansion in the application fields of information and communication technology (ICT) and cutting-edge electronic devices, extending into telecommunications, unmanned transport vehicles, and advanced national defense. Along with the rapid increase in component integration within electronic devices, the frequency bands used by each device are also expanding. Consequently, mutual interference caused by electromagnetic waves generated between electronic devices is becoming a critical issue, alongside the harmful effects on the human body resulting from exposure to electromagnetic waves and the advancement of ICT.
[0006] In the case of state-of-the-art, highly integrated electronic devices, the incidence of minute electromagnetic waves can cause performance degradation and malfunction, and for the stable operation of electronic equipment, electromagnetic interference (EMI) caused by electromagnetic waves generated from adjacent devices as well as electromagnetic waves applied from the outside must be eliminated.
[0008] The demand for electromagnetic shielding technology development and shielding materials is increasing significantly to improve the reliability of electronic devices and maintain excellent electronic signal precision by protecting against unintended electromagnetic waves.
[0010] Generally, electromagnetic shielding is achieved using conductive materials with high electrical and magnetic properties, with materials such as Cu and Al being widely utilized. Metal shielding materials offer advantages such as high strength, excellent shape stability, and very high shielding performance. However, since the application of materials with high specific gravity inevitably leads to an increase in product weight, there are limitations that make it difficult to apply them to drones and ground-based unmanned transport vehicles that require lightweight properties.
[0012] Magnesium alloys have the lowest density (1.78 g / cm³) among structural metal materials. 3 It has the characteristic of having mechanical strength equivalent to that of commercial Al alloys. Therefore, applying magnesium alloys as electromagnetic shielding materials can achieve product weight reduction.
[0014] To date, research on the electromagnetic shielding properties of magnesium alloys has mainly focused on cast and extruded materials, but for applications as lightweight case materials for transportation and communication equipment, they can be manufactured into rolled sheets to increase their utility.
[0016] Meanwhile, electromagnetic shielding metal materials containing magnesium mostly shield electromagnetic waves based on the principle of reflecting them from the metal surface, and most of the incident electromagnetic waves are reflected from the metal surface and to surrounding electronic devices It is authorized and highly likely to cause secondary EMI damage. Prior art literature
[0018] Korean Registered Patent No. 10-1145413 Korean Registered Patent No. 10-2042365 The problem to be solved
[0019] The objective of the present invention to solve the above-mentioned problems is to provide a lightweight, high-performance electromagnetic shielding material capable of simultaneously reflecting and absorbing electromagnetic waves by forming an amorphous metal sheet layer having electromagnetic wave absorption properties in order to reduce secondary electromagnetic damage caused by a magnesium plate, which is an electromagnetic shielding metal, and a method for manufacturing the same. means of solving the problem
[0021] The lightweight high-performance electromagnetic shielding material of the present invention for solving the above problem comprises a magnesium alloy plate and an amorphous metal sheet layer made of an amorphous metal composition having electromagnetic wave absorption properties on the magnesium alloy plate.
[0023] The above magnesium alloy plate is characterized by being a plate obtained by hot rolling a magnesium alloy base material.
[0025] The above amorphous metal composition is characterized by being a mixture of flake-shaped amorphous metal powder with a binder.
[0027] The method for manufacturing a lightweight, high-performance electromagnetic shielding material according to the present invention for solving the above problem comprises a step of preparing a magnesium alloy plate, a step of manufacturing an amorphous metal sheet using an amorphous metal composition having electromagnetic wave absorption properties, and a step of laminating the amorphous metal sheet manufactured on the magnesium alloy plate.
[0029] The above magnesium alloy sheet preparation step is characterized by hot rolling the magnesium alloy base material.
[0031] The amorphous metal composition of the above-mentioned amorphous metal sheet manufacturing step is characterized by being a mixture of flake-shaped amorphous metal powder with a binder. Effects of the invention
[0033] As described above, according to the lightweight high-performance electromagnetic shielding material and the method for manufacturing the same according to the present invention, in order to reduce secondary electromagnetic damage caused by a magnesium plate material which is an electromagnetic shielding metal, an amorphous metal sheet layer having electromagnetic absorption properties is formed, thereby enabling simultaneous reflection and absorption of electromagnetic waves. Brief explanation of the drawing
[0035] FIG. 1 is a schematic diagram showing the laminated structure of a lightweight, high-performance electromagnetic shielding material according to the present invention. FIG. 2 is an image showing the microstructure of a rolled AZ31 plate as an example of the method for manufacturing a lightweight high-performance electromagnetic shielding material according to the present invention. FIG. 3 is an SEM image of Fe-Si-B-Nb-Cu-based amorphous powder laminated by ball milling as an example of the method for manufacturing a lightweight high-performance electromagnetic shielding material according to the present invention. Figure 4 is an example of a method for manufacturing a lightweight, high-performance electromagnetic shielding material according to the present invention, showing the XRD diffraction analysis results of a flaked Fe-Si-B-Nb-Cu-based amorphous powder. FIG. 5 shows the electromagnetic shielding ability of a lightweight high-performance electromagnetic shielding material according to the present invention in the frequency band of 1.5 GHz to 10 GHz. FIG. 6 compares the electromagnetic shielding ability of rolled AZ31 sheet metal and recrystallized heat-treated AZ31 sheet metal applied to the lightweight high-performance electromagnetic shielding material according to the present invention, where (A) is for the frequency band: 30 MHz to 1.5 GHz and (B) is for the frequency band: 1.5 GHz to 10 GHz. Specific details for implementing the invention
[0036] The specific features and advantages of the present invention will be described in detail below with reference to the accompanying drawings. Prior to this, if it is determined that a detailed description of the functions and configurations related to the present invention may unnecessarily obscure the essence of the invention, such detailed description will be omitted.
[0038] The present invention relates to a lightweight high-performance electromagnetic shielding material and a method for manufacturing the same. More specifically, the invention relates to a lightweight high-performance electromagnetic shielding material capable of simultaneously reflecting and absorbing electromagnetic waves by forming an amorphous metal sheet layer having electromagnetic wave absorption properties to reduce secondary electromagnetic damage caused by a magnesium plate, which is an electromagnetic shielding metal, and a method for manufacturing the same.
[0040] Figure 1 shows a laminated structure of a lightweight, high-performance electromagnetic shielding material according to the present invention.
[0042] The lightweight high-performance electromagnetic shielding material according to the present invention comprises a magnesium alloy plate (100) and an amorphous metal sheet layer (200) made of an amorphous metal composition having electromagnetic wave absorption properties on the magnesium alloy plate.
[0044] The above magnesium alloy plate (100) has the characteristics of shielding electromagnetic waves through lightness and reflection of electromagnetic waves, and uses a magnesium alloy base material that has been hot-rolled.
[0046] The magnesium alloy may use at least one of the AZ-based (Mg-Al-Zn), Al-free Mg-Zn alloy, and Mg-Mn alloy. The magnesium alloy may contain other additional elements such as Fe, Cu, Ni, Zr, Si, Ca, and Ag, wherein the content of the other additional elements may be added at 10 wt% or less of the total alloy content of 100 wt%.
[0048] Preferably, the magnesium alloy may be AZ31 (Mg-3%Al-1%Zn-0.4%Mn).
[0050] Although magnesium alloys have been mentioned as representative materials for electromagnetic shielding, it is also possible to use other metal alloys that have lightweight properties and electromagnetic shielding characteristics, and preferably, aluminum alloys can be used as a substitute.
[0052] The above For the magnesium alloy, a rolled sheet obtained by hot-rolling a magnesium alloy base material may be used. Specifically, a cast material is manufactured by melting the magnesium alloy base material, pouring it into a mold, and solidifying and cooling it, and the cast material is rolled 8 to 15 times at 350 to 450°C with a reduction rate of 10 to 15% per rolling pass to manufacture a magnesium alloy sheet with a final thickness of 0.8 to 1.5 mm. However, the thickness of the magnesium alloy sheet may be appropriately designed considering the application and lightness, and is not limited thereto.
[0054] The magnesium alloy can undergo recrystallization heat treatment after hot rolling, and through the recrystallization heat treatment, the ductility of the magnesium alloy can be increased to increase sheet metal formability.
[0056] Recrystallization heat treatment can be performed at 350 to 400 ℃ for 30 to 90 minutes.
[0057] Grain coarsening may occur during the recrystallization heat treatment process, and since grain coarsening reduces grain boundaries and lowers the absorption and shielding performance of electromagnetic waves, the average size of the grains can be controlled so that it does not exceed 20 μm.
[0059] The amorphous metal sheet layer (200) is a sheet layer laminated on the magnesium alloy plate to absorb secondary electromagnetic waves generated by reflection from the magnesium alloy plate, and is made of an amorphous metal composition having electromagnetic wave absorption properties.
[0061] The above amorphous metal composition is a mixture of amorphous metal powder and a binder.
[0062] The above amorphous metal composition can be prepared by mixing an amorphous metal powder and a binder at 50 to 150 rpm for 5 to 20 minutes.
[0064] The above amorphous metal composition is prepared by mixing 25 to 40 parts by weight of a binder with 100 parts by weight of amorphous metal powder. At this time, if the binder is added in an amount less than 25 parts by weight, it is difficult to improve the strength of the amorphous metal sheet layer, and if it exceeds 40 parts by weight, the content of the amorphous metal powder becomes relatively low, which is disadvantageous in terms of electromagnetic shielding ability, so it is desirable not to exceed the above range.
[0066] More preferably, the amorphous metal composition can be prepared by mixing 30 to 35 parts by weight of a binder with 100 parts by weight of amorphous metal powder.
[0068] The binder above may be any one of synthetic rubber, fluoropolymer, phenolic resin, epoxy resin, and polyimide. As the synthetic rubber, either SBR (Styrene Butadiene Rubber) or BR (Polybutadiene Rubber) may be used, and as the fluoropolymer, FEP (Fluorinated Ethylene Propylene) may be used. Preferably, SBR may be used.
[0070] The above amorphous metal powder has no regular crystal structure and possesses scattering and absorption properties of electromagnetic waves, and may include at least one group among Fe-based, Co-based, Ni-based, Zr-based, Mg-based, Cu-based, and Al-based.
[0071] Preferably, Fe-based amorphous metal powder may be used, and specific examples of said Fe-based amorphous metal powder include at least one of Fe-Si-B-Nb-Cu, Fe-Si-B, Fe-B, and Fe-Ni-B. Most preferably, Fe-Si-B-Nb-Cu(FINEMET ® You can use TDK.
[0073] Amorphous metal powder was manufactured using an atomization method in which the prepared amorphous metal powder raw material was melted and the molten metal was flowed through a nozzle machined to a fine size. At this time, the amorphous metal powder had an average particle size (D 50 It is preferable to have a particle size of 10 to 20 μm, and under the above average particle size conditions, electromagnetic shielding ability can be improved by increasing the packing density while minimizing the contamination of the powder.
[0075] In particular, the average particle size (D of the above amorphous metal powder) 50If the particle size is less than 10 μm, the powder breaks easily during the subsequent lamination process, making it difficult to maintain the lamellar shape. Additionally, the packing density is low, and the contamination of the amorphous metal powder increases due to the large specific surface area, which lowers conductivity and increases magnetic loss, resulting in a decrease in electromagnetic wave absorption rate.
[0077] Subsequently, the manufactured amorphous metal powder was flaked through ball milling, and the aspect ratio of the flaked amorphous metal powder was set to 8 to 20, and preferably, one having an aspect ratio of 10 to 15 was used.
[0078] At this time, prior to proceeding with flake formation, the amorphous metal powder may be classified to 325 mesh to remove coarse powder.
[0080] Amorphous metal powders facilitate scattering and absorption of electromagnetic waves by allowing them to collide with a greater number of particles through flake formation. Additionally, since this increases packing density, the magnetic loss effect per unit volume can be maximized. In particular, Fe-based amorphous metal powders can further maximize this effect due to their high permeability.
[0082] For sheet formation of an amorphous metal composition, any one of the following methods may be used: doctor blade, compression molding, casting, and calendering. Preferably, a green sheet may be manufactured using a doctor blade, and the thickness of the sheet may be controlled by hot compression of the manufactured green sheet.
[0084] Specifically, an amorphous metal composition is evenly spread onto a flat plate using a doctor blade to form a green sheet, and the manufactured green sheet is dried to evaporate the solvent. Subsequently, the green sheet is placed between flat plate dies equipped with spacers for thickness control and subjected to hot compression.
[0086] At this time, drying of the green sheet is performed at 20 to 35°C for 12 to 36 hours, and hot compression can be performed at 120 to 170°C at a pressure of 8 to 15 MPa for 60 to 120 seconds.
[0088] The amorphous metal sheet layer (200) can be formed by stacking and hot-compressing n layers of green sheets. The electromagnetic shielding ability may be improved depending on the number of layers of green sheets, but since it is unsuitable for use as a lightweight component material if the weight increases, it can be formed with 1 to 4 layers or less.
[0090] An amorphous metal sheet layer is laminated onto a magnesium alloy plate, and the amorphous sheet layer can be bonded after applying a thin film of spray adhesive onto the magnesium alloy plate. At this time, the thickness of the adhesive application can be formed to be 10 to 100 μm.
[0092] The above spray adhesive is not limited to bonding a magnesium alloy and an amorphous metal sheet layer, but specifically may include at least one of rubber-based, polyurethane-based, acrylic-based, and epoxy-based adhesives, and preferably, a rubber-based spray adhesive may be used.
[0094] The thickness of the electromagnetic shielding material is not limited considering the intended use and shielding ability, but preferably, the thickness of the amorphous metal sheet layer can be formed to be 40 to 60% of the thickness of the magnesium alloy plate.
[0096] When used for drones and ground-based unmanned transport vehicles, the total thickness of the electromagnetic shielding material can be formed to be 2 mm or less.
[0098] Hereinafter, a method for manufacturing a lightweight, high-performance electromagnetic shielding material according to the present invention will be described.
[0100] A method for manufacturing a lightweight high-performance electromagnetic shielding material according to the present invention comprises a step of preparing a magnesium alloy plate, a step of manufacturing an amorphous metal sheet using an amorphous metal composition having electromagnetic wave absorption properties, and a step of laminating the amorphous metal sheet manufactured on the magnesium alloy plate.
[0102] In the magnesium alloy sheet preparation stage, a magnesium alloy sheet is prepared by hot-rolling a magnesium alloy base material.
[0104] Magnesium alloy plates are lightweight and have the characteristic of shielding electromagnetic waves through reflection of electromagnetic waves.
[0106] The magnesium alloy may use at least one of the AZ-based (Mg-Al-Zn), Al-free Mg-Zn alloy, and Mg-Mn alloy. The magnesium alloy may include other additional elements such as Fe, Cu, Ni, Zr, Si, Ca, and Ag, wherein the content of the other additional elements may be added at 10 wt% or less of the total alloy of 100 wt%.
[0108] Preferably, the magnesium alloy may be AZ31 (Mg-3%Al-1%Zn-0.4%Mn).
[0110] Although magnesium alloys have been mentioned as representative materials for electromagnetic shielding, it is also possible to use other metal alloys that are lightweight and have electromagnetic shielding properties, and preferably, aluminum alloys can be used as a substitute.
[0112] The above For the magnesium alloy, a rolled plate obtained by hot rolling a magnesium alloy base material can be used. Specifically, a cast material is manufactured by melting the magnesium alloy base material, pouring it into a mold, and solidifying and cooling it, and the cast material is rolled 8 to 15 times at 350 to 450°C with a reduction rate of 10 to 15% for each rolling pass to manufacture a plate with a final thickness of 0.8 to 1.5 mm.
[0114] The magnesium alloy can undergo recrystallization heat treatment after hot rolling, and through the recrystallization heat treatment, the ductility of the magnesium alloy can be increased to increase sheet metal formability.
[0116] Recrystallization heat treatment can be performed at 350 to 400 ℃ for 30 to 90 minutes.
[0117] Grain coarsening may occur during the recrystallization heat treatment process, and since grain coarsening reduces grain boundaries and degrades electromagnetic wave absorption and shielding performance, the average grain size can be controlled so as not to exceed 20 μm.
[0119] The amorphous metal sheet manufacturing step involves manufacturing an amorphous metal sheet using an amorphous metal composition having electromagnetic wave absorption properties, and includes a step of manufacturing an amorphous metal composition and a step of forming the manufactured amorphous metal composition into a sheet.
[0120] The amorphous metal sheet is laminated on the magnesium alloy plate and is a sheet layer for absorbing secondary electromagnetic waves generated by reflection from the magnesium alloy plate, and is composed of an amorphous metal composition having electromagnetic wave absorption properties.
[0122] In the step of manufacturing an amorphous metal composition, an amorphous metal composition is manufactured by mixing an amorphous metal powder and a binder, and the amorphous metal composition can be manufactured by mixing the amorphous metal powder and the binder at 50 to 150 rpm for 5 to 20 minutes.
[0124] The above amorphous metal composition is prepared by mixing 25 to 40 parts by weight of a binder with 100 parts by weight of amorphous metal powder. At this time, if the binder is added in an amount less than 25 parts by weight, it is difficult to improve the strength of the amorphous metal sheet layer, and if it exceeds 40 parts by weight, the content of the amorphous metal powder becomes relatively low, which is disadvantageous in terms of electromagnetic shielding ability, so it is desirable not to exceed the above range.
[0126] More preferably, the amorphous metal composition can be prepared by mixing 30 to 35 parts by weight of a binder with 100 parts by weight of amorphous metal powder.
[0128] The binder above may be any one of synthetic rubber, fluoropolymer, phenolic resin, epoxy resin, and polyimide. As the synthetic rubber, either SBR (Styrene Butadiene Rubber) or BR (Polybutadiene Rubber) may be used, and as the fluoropolymer, FEP (Fluorinated Ethylene Propylene) may be used. Preferably, SBR (styrene butadiene rubber) may be used.
[0130] The above amorphous metal powder has no regular crystal structure and possesses scattering and absorption properties of electromagnetic waves, and may include at least one group among Fe-based, Co-based, Ni-based, Zr-based, Mg-based, Cu-based, and Al-based.
[0131] Preferably, Fe-based amorphous metal powder may be used, and specific examples of said Fe-based amorphous metal powder include at least one of Fe-Si-B-Nb-Cu, Fe-Si-B, Fe-B, and Fe-Ni-B. Most preferably, Fe-Si-B-Nb-Cu(FINEMET ® You can use TDK.
[0133] Amorphous metal powder was manufactured using an atomization method in which the prepared amorphous metal powder raw material was melted and the molten metal was flowed through a nozzle machined to a fine size. At this time, the amorphous metal powder had an average particle size (D 50 It is preferable to have a particle size of 10 to 20 μm, and under the above average particle size conditions, electromagnetic shielding ability can be improved by increasing the packing density while minimizing the contamination of the powder.
[0135] In particular, the average particle size (D of the above amorphous metal powder) 50If the particle size is less than 10 μm, the powder breaks easily during the subsequent lamination process, making it difficult to maintain the lamellar shape. Additionally, the packing density is low, and the contamination of the amorphous metal powder increases due to the large specific surface area, which lowers conductivity and increases magnetic loss, resulting in a decrease in electromagnetic wave absorption rate.
[0137] Subsequently, the manufactured amorphous metal powder was flaked through ball milling, and the aspect ratio of the flaked amorphous metal powder was set to 8 to 20, and preferably, one having an aspect ratio of 10 to 15 was used.
[0138] At this time, prior to proceeding with flake formation, the amorphous metal powder may be classified to 325 mesh to remove coarse powder.
[0140] Amorphous metal powders facilitate scattering and absorption of electromagnetic waves by allowing them to collide with a greater number of particles through flake formation. Additionally, since this increases packing density, the magnetic loss effect per unit volume can be maximized. In particular, Fe-based amorphous metal powders can further maximize this effect due to their high permeability.
[0142] In the sheeting step, the amorphous metal composition is sheeted. For sheeting the amorphous metal composition, any one of the following methods may be used: doctor blade, compression molding, casting, and calendering. Preferably, a green sheet is manufactured using a doctor blade, and the thickness of the sheet can be controlled by hot-compressing the manufactured green sheet.
[0144] Specifically, an amorphous metal composition is evenly spread onto a flat plate using a doctor blade to form a green sheet, and the manufactured green sheet is dried to evaporate the solvent. Subsequently, the green sheet is placed between flat plate dies equipped with spacers for thickness control and subjected to hot compression.
[0146] At this time, drying of the green sheet is performed at 20 to 35°C for 12 to 36 hours, and hot compression can be performed at 120 to 170°C at a pressure of 8 to 15 MPa for 60 to 120 seconds.
[0148] The amorphous metal sheet layer (200) can be formed by stacking and hot-compressing n layers of green sheets. The electromagnetic shielding ability may be improved depending on the number of layers of green sheets, but since it is unsuitable for use as a lightweight component material if the weight increases, it can be formed with 1 to 4 layers or less.
[0150] In the lamination step, an amorphous metal sheet manufactured on the magnesium alloy plate is laminated.
[0152] In the above lamination step, an amorphous metal sheet layer is laminated onto a magnesium alloy plate, and the amorphous sheet layer can be bonded after applying a thin film of spray adhesive onto the magnesium alloy plate. At this time, the thickness of the adhesive application can be formed to be 10 to 100 μm.
[0154] The above spray adhesive is not limited to bonding a magnesium alloy and an amorphous metal sheet layer, but specifically may include at least one of rubber-based, polyurethane-based, acrylic-based, and epoxy-based adhesives, and preferably, a rubber-based spray adhesive may be used.
[0156] The thickness of the electromagnetic shielding material is not limited considering the intended use and shielding ability, but preferably, the thickness of the amorphous metal sheet layer can be formed to be 40 to 60% of the thickness of the magnesium alloy plate.
[0158] When used for drones and ground-based unmanned transport vehicles, the total thickness of the electromagnetic shielding material can be formed to be 2 mm or less.
[0160] The present invention will be described in detail below with reference to a preferred embodiment. However, the following embodiment is intended to specifically illustrate the present invention and is not limited thereto.
[0162] 1. Preparation of magnesium alloy
[0163] The casting of AZ31 base material was hot-rolled at 400°C. It was rolled 12 times with a reduction rate of 12% per rolling pass to produce a plate with a final thickness of 1 mm.
[0165] Figure 2 shows the microstructure of the rolled AZ31 plate, revealing severe intragrain lattice distortion due to significant deformation and the presence of numerous grain boundaries. The grain size was confirmed to be 10–15 μm, and the pH ranged from 85 to 200 MPa·cm⁻¹. 3 It showed a specific strength of / g.
[0167] The microstructure, formability, and electron shielding ability of the rolled sheet metal following recrystallization heat treatment were verified.
[0168] The re-curing heat treatment was performed on the rolled plate at 380°C for 1 hour, and then the deformation energy of the rolled plate was removed through furnace cooling.
[0170] It was confirmed that ductility increases after recrystallization heat treatment, which can improve the workability of the sheet metal.
[0172] The grain size is 10–20 μm, which is slightly increased compared to the rolled plate, but still has small grains, and Mg 17 Al 12 It was confirmed that the strength can be maintained by the existence of intermetallic compounds as a precipitate phase.
[0174] Figures 6 (A) and (B) show the electromagnetic shielding performance of rolled sheet metal and recrystallized heat-treated sheet metal in the frequency bands of 30 MHz to 1.5 GHz and 1.5 GHz to 10 GHz, respectively, with the rolled sheet metal showing about 5 to 10 dB better electromagnetic shielding performance compared to the recrystallized heat-treated sheet metal.
[0175] This is due to the fact that rolled sheets have more internal defects compared to recrystallized heat-treated sheets, allowing them to efficiently block incident electromagnetic waves.
[0177] Since recrystallization heat treatment improves the workability of the sheet metal but can cause a reduction in electromagnetic shielding ability, it was determined that it is desirable to control the grain size so that it does not exceed 20 μm. In the following experiments, rolled sheet metal was used.
[0179] 2. Preparation of amorphous metal alloy compositions
[0180] An amorphous metal alloy powder was prepared and mixed with an SBR (styrene butadiene rubber) binder to produce an amorphous metal alloy composition.
[0182] Amorphous metal alloy powder is Fe-Si-B-Nb-Cu alloy (FINEMET TM The raw material was melted, and the molten metal was manufactured using an atomization method.
[0183] Average particle size (D of amorphous metal powder) 50 ) used a powder with a particle size of 15㎛, and since coarse amorphous metal powder can act as an impurity, it was classified on a 325 mesh sieve and then milled for flake formation.
[0185] The amorphous metal powder was laminated using a ball mill to achieve an aspect ratio of 10 or greater, and after the lamination process, the average particle size (D) of the amorphous metal powder 50 ) was confirmed to be 14.27 μm.
[0187] Figure 3 shows a flake-shaped Fe-Si-B-Nb-Cu amorphous powder produced by ball milling, and Figure 4 shows the XRD diffraction analysis results of the flake-shaped Fe-Si-B-Nb-Cu amorphous powder.
[0189] Afterwards, 32.5 g of SBR binder was added per 100 g of flaked amorphous metal alloy powder, and stirring was performed at 50 rpm for 10 minutes to confirm that no bubbles in the mixture had been visually removed, and then stirring was stopped.
[0191] 3. Manufacturing and Lamination of Amorphous Metal Sheets
[0192] After applying the manufactured amorphous metal alloy composition to a flat plate, a green sheet of approximately 0.6 to 0.8 mm was produced using a doctor blade and dried at room temperature for 24 hours. Subsequently, a spacer with a thickness of 0.6 mm was installed between the upper and lower compression flat plate dies, and a sheet of 0.6 mm was produced by hot compression at 150°C at a pressure of 10 MPa (based on an area of 300 mm × 300 mm) for 90 seconds.
[0194] Subsequently, an electromagnetic shielding material was manufactured by applying a spray adhesive to one side of a magnesium alloy and then bonding the manufactured amorphous metal sheet.
[0196] Figure 5 shows the electromagnetic shielding ability of an amorphous metal sheet, a rolled AZ31 plate, and an electromagnetic shielding material laminated therewith in the frequency band of 1.5 GHz to 10 GHz.
[0197] The composite sheet showed an electromagnetic shielding ability approximately 10 dB higher than that of AZ31 plate in the measured frequency band.
[0198] As a result of measuring the absorption rate, it was shown that in the case of rolled AZ31, most of the electromagnetic waves were reflected and only 1% of the shielded electromagnetic waves were absorbed, whereas in the case of an electromagnetic shielding material laminated with amorphous metal sheets, 25% of the shielded electromagnetic waves were absorbed.
[0200] As described above, although the present invention has been explained with reference to the attached drawings and with reference to preferred embodiments, those skilled in the art may modify or vary the present invention in various ways without departing from the technical spirit and scope described in the claims of the present invention. Accordingly, the scope of the present invention should be interpreted by the claims described to include such many variations. Explanation of the symbols
[0202] 100 : Magnesium alloy plate 200: Amorphous metal sheet layer
Claims
Claim 1 The invention comprises a magnesium alloy plate and an amorphous metal sheet formed on the magnesium alloy plate, the amorphous metal sheet being composed of an amorphous metal composition having electromagnetic wave absorption properties, wherein the amorphous metal sheet is formed by forming a green sheet with an amorphous metal composition comprising a binder and flake-shaped amorphous metal powder, and then hot-compressing the green sheet at 120 to 170°C at a pressure of 8 to 15 MPa for 60 to 120 seconds, and wherein the flake-shaped amorphous metal powder has an average particle size (D 50 A lightweight, high-performance electromagnetic shielding material formed by laminating amorphous metal powder with a thickness of 10 to 20 μm, characterized by having a lamellar shape with an aspect ratio of 8 to 20. Claim 2 A lightweight, high-performance electromagnetic shielding material according to claim 1, characterized in that the magnesium alloy plate is a plate obtained by hot-rolling a magnesium alloy base material. Claim 3 delete Claim 4 The method comprises a step of preparing a magnesium alloy plate, a step of manufacturing an amorphous metal sheet using an amorphous metal composition having electromagnetic wave absorption properties, and a lamination step of laminating the manufactured amorphous metal sheet onto the magnesium alloy plate, wherein in the step of manufacturing the amorphous metal sheet, a green sheet is formed using an amorphous metal composition comprising a binder and flaked amorphous metal powder, and then the green sheet is hot-compressed at 120 to 170°C at a pressure of 8 to 15 MPa for 60 to 120 seconds to form an amorphous metal sheet, and the flaked amorphous metal powder has an average particle size (D 50 A method for manufacturing a lightweight, high-performance electromagnetic shielding material characterized by being formed by laminating amorphous metal powder of 10 to 20 μm, and having a lamellar shape with an aspect ratio of 8 to 20. Claim 5 A method for manufacturing a lightweight, high-performance electromagnetic shielding material, wherein, in claim 4, the magnesium alloy plate preparation step is characterized by hot rolling a magnesium alloy base material. Claim 6 delete
Citation Information
Patent Citations
Film for absorption and shielding EMI and method for manufacturing the same, Cable having film for absorption and shielding EMI
KR1020090027807A
Electronics especially laptop computer case inserted magnesium panel using insert injection molding
KR2020100000706U